2006
DOI: 10.1111/j.1745-7254.2006.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin on methylglyoxal-induced oxidative DNA damage and cell injury in human mononuclear cells

Abstract: Aim: To examine the effect of curcumin on oxidative DNA damage and cell apoptosis and injury caused by the reaction of methylglyoxal(MG) with amino acids. Methods: We used DNA strand breaks to examine the effect of curcumin on oxidative DNA damage. In addition, reactive oxygen species(ROS) formation occurs in MG‐treated mononuclear cells, so the effect of curcumin on ROS generation was measured using 2′,7′‐dichlorofluorescin diacetate(DCF‐DA) as the detection reagent. Moreover, the impact effects of curcumin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…In vitro studies have also reported Cur-related modulation of arsenic-induced genotoxicity in human lymphocytes (Sinha et al, 2009). Along these lines, Cur was also found to be effective in preventing methylglyoxal (MG)-induced oxidative DNA damage, cell injury, apoptosis, and generation of ROS in mononuclear cells (Chan and Wu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also reported Cur-related modulation of arsenic-induced genotoxicity in human lymphocytes (Sinha et al, 2009). Along these lines, Cur was also found to be effective in preventing methylglyoxal (MG)-induced oxidative DNA damage, cell injury, apoptosis, and generation of ROS in mononuclear cells (Chan and Wu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragmentation has been utilized as a characteristic feature of apoptosis [50]. conducted by Ryu Ar et al, [53], Madkour NK [54] Zhu YG et al, [55], Chan WH et al, [56], who stated that curcumin can also inhibit the oxidative DNA damage by Chrysotile, Lambda cyhalothrin, tertbutyl hydroperoxide (t-BHP) and Methylglyoxal respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a potent scavenger of a variety of reactive oxygen species including superoxide anion radicals, hydroxyl radicals and inhibit lipid peroxidation and effectively block thiol depletion (Chattopadhyay et al, 2005). Furthermore, Curcumin was also found to be effective in preventing methylglyoxal (MG)-induced oxidative DNA damage, cell injury, apoptosis, and generation of ROS in mononuclear cells (Chan and Wu, 2006) .…”
Section: Concurrent Administration Of Curcumin Mitigates Arsenic -Andmentioning
confidence: 99%